Connecting to the religious heritage in Amal Donqul’s poetry collection Al’ahd Alati - Sarahneh, Sara Hussein (Journal of Humanities & Social Sciences, 2020)
This study aimed at searching in religious heritage in Amal Donqol collection of poems in his period. This poet is known with his national views and attitudes connected with steadfastness firmness and not giving up. The study showed how the poet affected by Quran, prophets personalities and religious stories, Torah, Gospel heritage. The researcher tries to get inspiration from religious symbol to see it in real world through meanings and symbols. She used collective way in presenting and analyzing the poem showing the poet communication with heritage, showing words meanings and indications trying to criticize and to comment on texts to show the poet aim.